Anterior Segment Imaging in Glaucoma. (22nd May 2013) - Salim, Sarwat; Dorairaj, Syril
Abstract: Anterior segment imaging allows objective assessment of the anterior segment of the eye, particularly the anterior chamber angle. Both qualitative and quantitative analyses are possible and aid in detecting and managing closed-angle and open-angle mechanisms in various forms of glaucoma. This review focuses primarily on anterior segment optical coherence tomography and ultrasound biomicroscopy, with emphasis on principles of technology, commercially available devices, and clinical applications in glaucoma with potential advantages and disadvantages of each technology.